Non-Performing Financing sebagai Mediasi dalam Hubungan Pembiayaan Syariah dan Profitabilitas Bank Umum Syariah di Indonesia - Dewi, Risma Arlia Sinta; Utami, Yuni; Amirah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to examine the extent to which Sharia-based financing—comprising murabahah, musyarakah, mudharabah, qard, istishna, and ijarah contracts—affects the profitability of Islamic Commercial Banks in Indonesia, with non-performing financing (NPF) serving as a mediating variable.Data were collected from annual reports, the official websites of the OJK, IDX, and sample companies during the period 2020–2024, then analyzed using multiple linear regression and path analysis. The regression results indicate that all types of financing significantly influence profitability, with the largest contribution coming from istishna (β = 96.277; p < 0.001), followed by musyarakah (β = 71.895; p < 0.001), and mudharabah (β = 39.244; p < 0.001). Conversely, ijarah shows a negative effect on profitability (β = –2.598; p = 0.034). Regression analysis of NPF indicates that mudharabah, istishna, and ijarah have a significant positive effect on NPF, while murabahah, musyarakah, and qard have no significant effect. Path testing reveals that there is no mediation of NPF in the relationship between murabahah and profitability. However, significant mediation by NPF was found in the relationship between musyarakah, mudharabah, qard, istishna, and ijarah on profitability. These findings confirm that the effectiveness of Islamic financing in improving profitability is not only determined by the type of contract used but also highly dependent on the quality of financing risk management reflected in the NPF level.